Dimerization of α-pinene, using Phosphotungstic acid supported on SiO2 as catalyst - Merino, Nora Andrea (2014)
The α-pinene dimerization in liquid phase was studied by using phosphotungstic acid catalysts H3PW12O40, (HPW) supported on commercial silica. These catalysts were characterized by XRD, FT-IR and FT-IR of pyridine adsorbed. Catalyst characterization by XRD showed the presence of HPW crystals on HPWSi catalyst. FT-IR spectra showed only bands assigned to the pyridine adsorption on Bronsted acid sites. The catalytic activity was found to depend on the reaction temperature and the amount of catalyst loaded in the reactor, and the highest selectivity in dimers corresponded to the HPW supported. Under reaction conditions 130ºC and 4% catalyst, the most active catalyst showed 100% α -pinene conversion and 55% selectivity to dimers. The selectivity to dimers increases with the increase of the reaction temperature and the amount of catalyst loaded in the reactor.